PERCEPATAN PERGERAKAN TANAH MAKSIMUM DAERAH CEKUNGAN BANDUNG: STUDI KASUS GEMPA SESAR LEMBANG - Lina Handayani; D. Mulyadi; Dadan D Wardhana; Wawan H.Nur (Pusat Survei Geologi, 2009)
The highly populated Bandung Basin needs a seismic hazard map, especially due to the existence of Lembang Fault on the north of the area. In this paper, the seismic hazard map was constructed based on calculation of peak ground acceleration (PGA) using Booreâ€™s (1997) empirical attenuation relationship. The model was an assumed earthquake with moment magnitude (Mw) of 6 that was caused by Lembang Fault activity. Data input consists of velocity of seismic wave S, that was obtained through geological unit classification. The result shows three zones with highest PGA values: near the seismic source, lowland at the south of Bandung, and a small area at the west of Bandung.The most significant factors on high PGA values are the distance from the source of an earthquake and the geological unit of an area.Â Keywords: peak ground acceleration, Lembang Fault, Bandung BasinÂ